Implementasi Sikap Siswa Terhadap Pertemanan Di Lingkungan SDIT Rumah Anak Soleh - Yusnan, Muhammad; Rumiati; Abal, Dian Nita; Nasria; Murniati (CV. SINAR HOWUHOWU, 2025)
This study aims to improve the self-expression of quiet students through structured psychological In school social life, friendship plays a crucial role in shaping students' character, including tolerance, empathy, cooperation, and social responsibility. This study aims to describe the implementation of student attitudes toward friendship within the Rumah Anak Soleh Islamic Elementary School (SDIT). This research used a descriptive qualitative approach through observation, interviews, and documentation of third-grade students at Rumah Anak Soleh Elementary School. The results demonstrate positive attitudes toward friendship, such as helping each other, respecting differences, and resolving conflicts through open communication.